Pengaruh Diversifikasi Usaha dan Volume Perdagangan Saham terhadap Return Saham pada Perusahaan Sub Sektor Farmasi (Bursa Efek Indonesia 2018-2022) - Maharani, Septia Putri (Value : Journal of Management and Business, 2023)
Provision of drugs and medical devices to the public is the focus of the pharmaceutical industry. The pharmaceutical industry has been badly affected by the COVID-19 pandemic due to its relationship with health. The purpose of this study was to find out how business diversification and trading volume activity impacted stock returns for pharmaceutical companies listed on the IDX from 2018 to 2022. 40 data were collected using a purposive sampling technique and an observation period of 5 years. Descriptive and verification analyzes were performed, including classical assumptions (normality, heteroscedasticity, autocorrelation and multicollinearity), multiple linear regression analysis, t-test and f-test. Data processing was carried out using SPSS 26 statistics. The results of testing the data show that Business Diversification (X1) does not partially affect Stock Returns, and Trading Volume Activity (X2) partially affects Stock Returns. Furthermore, business diversification (X1) and trading volume activity (X2) affect stock returns simultaneously. Keywords: Pharmaceutical Industry, Business Diversification (X1), Trading Volume Activity (X2), Stock Returns.